Exploring the importance of vocabulary for English as an additional language learners’ reading comprehension - Brooks, Gavin; Clenton, Jon; Fraser, Simon (Studies in Second Language Learning and Teaching, 2021)
This exploratory study represents an attempt to investigate the factors that may affect the reading comprehension abilities of English as an additional language (EAL) learners. For this study, we examined a participant group of 31 (25 EAL and 6 first language English) learners studying at an international school in Japan. We assessed the participants according to four factors shown to influence reading comprehension: vocabulary knowledge, word decoding skills, reading fluency, and general linguistic ability. Our results show that differences in vocabulary knowledge show more variance in reading comprehension scores than the other factors examined in this study, highlighting the importance of vocabulary knowledge for reading comprehension. However, other factors such as reading fluency and general linguistic knowledge are also shown to be moderate to strong predictors of reading comprehension. Based on these results, we suggest that EAL learners need targeted language support to enhance academic text comprehension.